2014
DOI: 10.1111/jog.12320
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of palliative chemotherapy and hospice enrollment in late‐stage ovarian cancer patients

Abstract: Chemotherapy after 1st Ref can be offered and hospice enrollment during the terminal stages is encouraged for recurrent ovarian cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…A retrospective study compared chemotherapy and supportive care in patients with platinum-resistant ovarian cancer after the first disease progression. The authors concluded that chemotherapy conferred no survival benefit over supportive care [4]. Another study also concluded that aggressive care did not result in improved survival.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study compared chemotherapy and supportive care in patients with platinum-resistant ovarian cancer after the first disease progression. The authors concluded that chemotherapy conferred no survival benefit over supportive care [4]. Another study also concluded that aggressive care did not result in improved survival.…”
Section: Plos Onementioning
confidence: 99%
“…For recurrent or refractory ovarian cancers, the goals of chemotherapy include palliation of disease-related symptoms and improvement of quality of life with minimum chemotherapy-related side effects [3]. However, limited data are available regarding the optimal timing for initiation of palliative chemotherapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…As chemotherapy is typically discontinued following resistance, few patients with refractory disease are eligible for such studies, and small numbers of female patients included (49). Another limitation is that cytotoxic regimens differ between patients, doses are frequently altered and patients are not randomised.…”
Section: Clinical Papersmentioning
confidence: 99%
“…Disclosures The authors report no disclosures or con icts of interest. JCSO 2016;14 (12):501-508. ©2016 Frontline Medical Communications.…”
mentioning
confidence: 99%
“…Palliative chemotherapy can certainly prolong survival and improve quality of life for patients with cancers such as colorectal and ovarian cancers. 11,12 Patients' assessment of that bene t on an individual basis after experiencing the treatment is not known. We hypothesized that exploring the retrospective vantage point may o er assessments of the key question that patients face, namely whether taking palliative chemotherapy is worthwhile or not.…”
mentioning
confidence: 99%